Uji komparasi desinfektan septalkan, terralin, dan alkohol 70% terhadap daya sterilisasi permukaan kursi dental - Arif Andriyanto; Risma Dwi Irfanto; Heribertus Dedy Kusuma Yulianto (Jurnal Teknosains, 2023)
Cross-infection has the potential to occur in the Dental and Oral Hospital due to cross-transmission of pathogenic microbes through dental chair surfaces that are contaminated with microbes. This  study aims to compare the effectiveness of three types of disinfectant Septalcan, Terralin, and 70% alcohol on the inhibition of pathogenic microbes originating from the oral cavity of patients who contaminate the surface of dental chairs in aerosol and non-aerosol clinics. Sampling of microorganisms was carried out using the technique of wiping/swab the surface of dental chairs in aerosol and non-aerosol clinics before and after the disinfection process with three types of disinfectants. The decrease in the number of germs before and after the disinfectant process is used as a parameter for the effectiveness of the disinfectant. The results of the one-way ANOVA statistical test shows that there is no significant difference in the effectiveness of the three types of Septalcan, Terralin, and 70% alcohol in reducing the number of germs on the surface of dental chairs. The three types of disinfectants are able to minimize the risk of cross-infection due to pathogenic microbial contamination on the surface of the dental chair.